Designing a warehouse management information system : (Cases Study: PT. Fatijja Digital Indonesia) - Hamidah Hamidah; Verdi Yasin; Rumadi Hartawan; Anton Zulkarnain Sianipar (Journal of Mathematics and Technology (MATECH), 2022)
The inventory system is a very important asset for every company. Inventory is a problem that is often faced by PT. Fatijja Digital Indonesia because the processing of data that is still manual is enough to hinder a work process that takes place so that there are often mistakes in calculating the stock of goods, recording outgoing goods, recording incoming goods, making invoices and month-end reports, for that the company needs an inventory application system using a MySQL database that can solve all existing problems, So that admins can carry out all activities to be effective and efficient. In developing this system, researchers used the waterfall method. The result of this study is a web-based inventory application system that is expected to make it easier for admins to manage incoming and outgoing goods